Study of the Utilization Efficiency and Its Influencing Factors of Water Resources in Yangtze River Economic Belt. (June 2020) - Xu, Sichen; Liang, Hao
Abstract: The Yangtze River Economic Belt has gradually become one of the regions with the strongest comprehensive strength and the greatest strategic competitiveness in China. Promoting the utilization efficiency of water resources in various provinces and cities in this region and minimizing the restraint effect of insufficient utilization of water resources on the economy can provide strong support for the development of the region from the perspective of water resources. The SBM model was used to measure the water use efficiency of 11 provinces and cities in the Yangtze River Economic Zone from 2007 to 2017 and Tobit model was used to identify the key influencing factors. The results show that the water use efficiency of the provinces and cities in the Yangtze River Economic Zone varies greatly, and the total factor productivity index of water resources shows an overall growth trend, which is mainly determined by the scale efficiency. The per capita GDP and the proportion of the first industry have a significant positive effect on the water use efficiency, while the government's investment in water resources and per capita water resources endowment have a significant negative correlation. Based on this, some countermeasures and suggestions are put forward, such as strengthening inter-regional technical cooperation, optimizing water use structure, and reasonably investing in water conservancy facilities projects.